2021
DOI: 10.1021/acs.jchemed.1c00439
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Implementing VR2E2C, a Virtual Reality Remote Education for Experimental Chemistry System

Abstract: In this work, we introduce the VR2E2C system for Virtual Reality Remote Education for Experimental Chemistry. It aims to increase scientific literacy about remote education of theoretical and experimental chemistry among the public and high school students. It provides a laboratory option for students with disabilities who are keen on chemistry experiments but have limited mobility. VR2E2C provides three modes to accomplish the training: users can choose to control the intelligent robot to finish the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…Nevertheless, ICT advances for education helped in many ways to the application of authentic assessment in these social distance times. There are several studies about the use of new generation technology for learning like immersive simulation scenarios, virtual reality, 360 video and augmented reality applications that give some support to the learning progress of students in virtual scenarios for different disciplines (Badowski et al, 2021;Lu et al, 2021) These studies' common point of view is that students get near complex real-life situations they need to understand and solve. The effect of immersion they experience while using these applications is quite good for developing high order thinking and problem-solving performance.…”
Section: Performance and Authentic Assessment For Competency-based Le...mentioning
confidence: 99%
“…Nevertheless, ICT advances for education helped in many ways to the application of authentic assessment in these social distance times. There are several studies about the use of new generation technology for learning like immersive simulation scenarios, virtual reality, 360 video and augmented reality applications that give some support to the learning progress of students in virtual scenarios for different disciplines (Badowski et al, 2021;Lu et al, 2021) These studies' common point of view is that students get near complex real-life situations they need to understand and solve. The effect of immersion they experience while using these applications is quite good for developing high order thinking and problem-solving performance.…”
Section: Performance and Authentic Assessment For Competency-based Le...mentioning
confidence: 99%
“… 32 The recently developed Virtual Reality Remote Education for Experimental Chemistry (VR 2 E 2 C) system features both a digital interface and real-lab live-stream, which give students control over the experiment and the opportunity to virtually observe an in-person experiment. 85 Digitization of the lab environment and high interactivity that comes with it gives users a very close experience to in-person laboratories without the associated safety concerns. Overall, this translation allows for engagement with exploratory educational activities in chemistry that can enhance independent, discovery-based learning.…”
Section: Virtual Learning Paradigmmentioning
confidence: 99%
“…This approach has been most extensively explored as a forum for interactive molecule visualization, which has allowed students to interact with an otherwise inaccessible molecular world. Within a laboratory setting, VR has been applied to both instrumentation-based (e.g., IR spectroscopy and pH meter) at NC State University and Iowa State University and synthetic experiments (e.g., synthesis of gold nanocrystals) at the Chinese University of Hong Kong. ,, The results from NC State University showed that there were no significant differences in learning outcomes between the group of students that experienced and performed the VR lab and the group that did the same experiment in a traditional lab . The recently developed Virtual Reality Remote Education for Experimental Chemistry (VR 2 E 2 C) system features both a digital interface and real-lab live-stream, which give students control over the experiment and the opportunity to virtually observe an in-person experiment . Digitization of the lab environment and high interactivity that comes with it gives users a very close experience to in-person laboratories without the associated safety concerns.…”
Section: Virtual Learning Paradigmmentioning
confidence: 99%
“…Even though VR technology has only recently entered the field of chemistry education, many activities, , demonstrations, experiences, , and games , have already been developed. In particular, some tools allow users to interact with and manipulate the 3D structures of molecules, feel the formation of a chemical bond through the vibration in the fingertips of the haptic glove, or perform the experiments in the copycat chemistry laboratory. , Other more specialized VR experiences include placing students in the virtual crime scene for subsequent evidence collection and analysis, conducting virtual field trips overseas for environmental chemistry projects, constructing enzyme structures and performing real-time interactive molecular dynamics simulations on them, demonstrating the practical application of nuclear chemistry in medicine, and teaching about metal coordination chemistry and molecular orbitals .…”
Section: Introductionmentioning
confidence: 99%